Co-development strategy for successful recruitment of patients to a qualitative research study on compassion in a UK inpatient hospice. Issue 3 (1st September 2016) - Armour, Kathy; Grubb, Rachel; Palfrey, Hannah; Ives, Jonathan
Abstract : Background: An empirical bioethics analysis exploring what palliative inpatients understand as compassion was planned within an Intercalated BMedSc degree. Limited time was available, so to achieve deadlines, a co-developmental approach was employed maximising clinical/research expertise from hospice and university. Aim: To study compassion by forming an effective university-hospice research partnership. Methods: A multi-disciplinary research team (MDRT) was created comprising a student, academic researcher, hospice nurse and hospice facilitator. Introductory meetings in January 2016 developed a research strategy appropriate to a hospice inpatient unit (IPU). Three members of the MDRT attended the IRAS committee and on-going support ensured governance permissions were obtained. Recruitment over 8 weeks (March–May 2016) was designed to be symbiotic with clinical care, promoting a good experience of exploratory qualitative interviewing. Results and discussion: Intense support of the researcher facilitated timely transition through governance. All IPU patients were screened. Nineteen eligible patients were approached and introduced to the study by the nurse who also communicated with the clinical care teams. Six patients were consented by the student and 15–25 minute semi-structured interviews were conducted. Reasons for non-participation varied from feeling tired or poorly to exclusive interest in interventional research trials. Conclusion: A MDRT approach can facilitate a qualitative research study in an inpatient hospice. Knowledge of the clinical setting maximised an effective recruitment strategy. Recruitment barriers included time constraints, patient willingness, patient availability, and perceptions of patient capacity and willingness. Ethics and procedural questions around promoting compassion research participation in this potentially vulnerable population can be addressed. Reference: Byrne A, Upton L, Townsend S. Mind the gap: a step forward in supporting hospice-based research. BMJ Support Palliat Care 2014;5 (1):4–6. doi:10.1136/bmjspcare-2014-000808